IMPLEMENTASI UNDANG-UNDANG NO. 7 TAHUN 1967 TENTANG VETERAN REPUBLIK INDONESIA DI BANDAR LAMPUNG - Ina Novianti; Iskandar Syah; Maskun Maskun (FKIP UNIVERSITAS LAMPUNG, 2013)
Abstract: The implementation of government regulation No. 7, 1967 about Veteran ofRepublic of Indonesia in Bandar Lampung. Independence of the Republic of Indonesia is theresult of the struggle of the hero. Heroes, those who are still alive called Veterans. Award givenby the government in the form of benefits to Veterans. Allowances is set out in Article 9 of LawNo. 7, 1967 on the right of Veteran Republic of Indonesia set out in government regulations andregulatory president. So that the implementation of the provision of benefits based on thegovernment rules and regulations president. Is intended to determine how the implementation ofGovernment Regulation No. 7 1967 about the right of Veteran of Republic of Indonesia inBandar Lampung chapter 9. Based on data obtained in the field and interviews with seveninformants about Veterans benefits contained in the regulations in accordance with the fundsreceived by the Veterans, honor funds contained in the presidential decree in accordance withthe funds received by Veterans, health benefits provided by the goverment in accordance withthe received by Veterans, provision of transport provided by the Veterans as received byVeterans and received tax relief given by the goverment in accordance with the received byVeteran. So it can be concluded that the implementation of Government Regulation No. 7 1967about the right of Veteran of Republic of Indonesia in Bandar Lampung chapter 9 is realized inthe form of allowances set out in goverment rules and regulations Veteran received the presidenwith the Republik of Indonesia in Bandar Lampung is appropriate.Keywords : The Veteran of Republic IndonesiaABSTRAKAbstrak: Implementasi Undang-Undang No. 7 Tahun 1967 tentang Veteran RepublikIndonesia di Bandar Lampung. Kemerdekaan Negara Republik Indonesia adalah hasilperjuangan dari pahlawan. Pahlawan ini, bagi yang masih hidup disebut Veteran. Penghargaanyang diberikan oleh pemerintah kepada Veteran yaitu berupa tunjangan yang tertera dalampasal 9 Undang-Undang No. 7 tahun 1967 tentang hak Veteran Republik Indonesia. Besarnyatunjangan tertuang pada Peraturan Pemerintah dan Peraturan Presiden. Sehingga pelaksanaanpemberian tunjangan Veteran berpedoman pada Peraturan Pemerintah dan Peraturan Presiden.Maka, penelitian ini ditujukan untuk mencari tahu bagaimanakah pelaksanaan Undang-UndangNo. 7 tahun 1967 tentang hak Veteran Republik Indonesia Pasal 9 di Bandar Lampung.Berdasarkan data yang diperoleh di lapangan dan hasil wawancara dengan 7 informan tentangtunjangan veteran yang tertuang dalam Peraturan Pemerintah sesuai dengan dana yang diterimaVeteran, dana kehormatan yang tertuang dalam Peraturan Presiden sesuai dengan dana yangditerima Veteran, tunjangan kesehatan yang diberikan oleh pemerintah sesuai dengan yangditerima Veteran, penyediaan transportasi yang diberikan oleh pemerintah sesuai dengan yangditerima Veteran dan keringanan pajak yang diberikan pemerintah sesuai dengan yang diterimaVeteran. Jadi dapat disimpulkan bahwa Implementasi dari Undang-Undang No. 7 Tahun 1967tentang hak Veteran Republik Indonesia Pasal 9 di Bandar Lampung direalisasikan dalambentuk tunjangan-tunjangan dan tunjangan yang tertuang dalam Peraturan Pemerintah danPeraturan Presiden dengan yang diterima Veteran Republik Indonesia di Bandar Lampungadalah sesuai.Kata Kunci : Veteran Republik Indonesia